2017
DOI: 10.1002/jib.431
|View full text |Cite
|
Sign up to set email alerts
|

Determination of γ -aminobutyric acid in Chinese rice wines and its evolution during fermentation

Abstract: γ‐Aminobutyric acid (GABA) is a functional amino acid that is widely present in Chinese rice wine. In this study, high‐performance liquid chromatography coupled with ultraviolet detection (HPLC‐UV) was established for the determination of γ‐aminobutyric acid in 22 Chinese rice wines collected from the Shaoxing region of China. Furthermore, the evolution of GABA was studied in Chinese rice wine during primary and post‐fermentation process. Results showed that the HPLC method was reliable with good linearity, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This may be because the yeasts obtained sufficient nutrients from the primary fermentation and as a result did not consume GABA as a nitrogen source post‐fermentation. The increase in GABA content in these rice wines at the end of the post‐fermentation process is likely to be from the autolysis of yeast .…”
Section: Resultsmentioning
confidence: 99%
“…This may be because the yeasts obtained sufficient nutrients from the primary fermentation and as a result did not consume GABA as a nitrogen source post‐fermentation. The increase in GABA content in these rice wines at the end of the post‐fermentation process is likely to be from the autolysis of yeast .…”
Section: Resultsmentioning
confidence: 99%
“…Huangjiu, a traditional fermented food with multi-strain mixed fermentation, is recognized as one of the three ancient wines globally, together with beer and grape wine. The abundant nutrients and bioactive compounds were produced during the long-term brewing process under the unique bilateral fermentation and micro-ecosystem of Huangjiu [ 25 , 28 , 41 , 42 ]. Functional analysis of Huangjiu NAC evaluated their beneficial effects on antioxidant, immunomodulatory, anti-tumor, atherosclerosis prevention, gut microbiota restoration, and intestinal micro-ecology improvement [ 25 , 28 , 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that GABA-rich foods such as tea [28,29], rice germ [30], and fermented soybeans [31] can reduce the incidence of insomnia and depression and improve symptoms associated with chronic alcoholism [32]. Studies have shown that yellow wine is rich in GABA and can be used as a source of food with high GABA content [33]. In this work, we determined the GABA content in rice wines brewed by adding different concentrations of TrF, and the results (Figure 3) show that TrF significantly enhances the GABA content in rice wine, with a positive correlation (r = 0.913, p < 0.01).…”
Section: Effect Of Trf Addition On Gaba Content Of Rice Winementioning
confidence: 99%